Efficacy of the combination of P5 peptide and photodynamic therapy mediated by bixin and chlorin-e6 against Cutibacterium acnes biofilm - Pereira, Felipe [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Lopes, Thais de Assis; de Oliveira, Kleber Thiago; Cilli, Eduardo Maffud [UNESP]; Barbugli, Paula Aboud [UNESP]; Fontana, Carla Raquel [UNESP] (Elsevier, 2022)
In this study, the action of antimicrobial peptide (AMP) P5 and antimicrobial photodynamic therapy (aPDT) mediated by bixin and chlorin-e6 (Ce6) on Cutibacterium acnes (C. acnes) in planktonic phase and biofilm were evaluated both as monotherapies and combined therapies. Microbial viability after treatments were quantified by colony-forming units per milliliter of the sample (CFU/mL) and have demonstrated that all treatments employed exerted bactericidal activity, reducing the microbial load by more than 3 log10 CFU/mL, also demonstrating for the first time in the literature the antimicrobial photodynamic effect of bixin that occurs mostly through type I mechanism which was proved by the quantification of superoxide anion production. Bacterial biofilm was completely eliminated only after its exposure to aPDT mediated by this PS, however, Ce6 proved to be a more efficient PS, considering that most of the photodynamic effect of bixin- aPDT was exerted by excitation of the endogenous C porphyrins of C. acnes with blue light. The combination of P5 with Ce6-aPDT showed a synergistic effect on the bacterial biofilm with a reduction in microbial load by more than 10 log10 CFU/mL, in which the ability of P5 to permeabilize the polymeric extracellular matrix of the biofilm explains the obtained results, with greater internalization of the PS as shown by the Confocal Laser Scanning Microscopy. One-way ANOVA (Analysis of Variance) with Tukey's post-test and two-way ANOVA with Bonferroni's post-test were used to compare the values of continuous variables between the control group and the treatment groups.
Keywords: antimicrobial peptides; bixin; chlorin-e6; Cutibacterium acnes; P5; Photodynamic therapy; synergism